International responsibility to protect the environment from transboundary pollution - Majeed Hamid, . Assistant Lecturer Moayad (The college of law and political science journal, 2023)
7KH DLP RIWKH UHVHDUFK LV WR LGHQWLI\WKH GHÀQLWLRQ RIWKH HQYLURQPHQW DQGits characteristics, as well as to identify the nature of pollution and its sources,WRLGHQWLI\WKHGHÀQLWLRQRILQWHUQDWLRQDOUHVSRQVLELOLW\RIWKHHQYLURQPHQWDQGLWVconditions, and to identify compensation for cross-border environmental damageand international satisfaction . The descriptive approach was used in the analyticalmethod . It was concluded that maintaining a pure and pollution-free environmentand protecting those affected by this pollution is currently a global requirementWKDW DLPV  WR VHW VWULFW OHJDO UXOHV LQ WKH ÀHOG RI HQYLURQPHQWDO SURWHFWLRQ IURPpollution. The cross-border damage is a relatively recent and was not consideredby the international legislator until the beginning of the seventies of the last centurythe compensation for cross-border environmental damage must be effective, fairDQGVXIÀFLHQWWRFRPSHQVDWHIRUWKHHQYLURQPHQWDOGDPDJH